(untitled) (Bangladesh Heart Journal, 2019)
Background: We examined the hypothesis that high blood lactate level in intensive care unit patient after adult cardiac surgery under cardiopulmonary bypass is associated with early adverse outcome. The objective of this study was to evaluate whether high blood lactate level after cardiac surgery is a predictor of the early outcome after adult cardiac surgery under cardiopulmonary bypass. Methods: This prospective observational study was carried out in the department of Cardiac Surgery at National Institute of Cardiovascular Disease (NICVD), Dhaka from July, 2013 to April 2014. A total number of 100 patients who underwent cardiac operation with cardiopulmonary bypass were enrolled in this study as per inclusion and exclusion criteria. Patients were divided into two groups according to their blood lactate level 6 hours after transferintensive care unit. Peroperative variables and postoperative variables were observed and recorded during the hospital course of patient. Categorical variables were analyzed by Chi- Square test and Fisher’s exact test and continuous variables were analyzed by ‘t’ test. Multiple Binary Logistic Regression Analysis of predictors for each of the outcome variables was done. Results: Blood lactate levels ≥3mmol/L 6 hours after transfer to intensive care unit were present in 57(57%) patients. Multiple logistic regression analysis showed higher blood lactate level was an independent predictor for early postoperative low output syndrome (OR 9.073, 95% CI 2.819 – 29.207, p = < .0001), pulmonary complication (OR 5.734, 95% CI 1.814 – 18.122, p = .003), neurological deficits (OR 9.725, 95% CI 1.111 - 85.147, p = .040), renal dysfunction (OR 7.393, 95% CI 1.855-29.469, p = .005), arrhythmia (OR 10.512, 95% CI 1.902 – 58.108, p = .007) and wound infection (OR 7.742, 95% CI 1.418 - 42.259, p = .018). Conclusions: High blood lactate level 6 hours after transfer to intensive care unit is an independent predictor for worse outcomes in adult patients after cardiac surgery under cardiopulmonary bypass. Bangladesh Heart Journal 2019; 34(1) : 25-30